The performance of concrete containing fine recycled concrete aggregate (FRCA) and fine crumb rubber (FCR) as partial fine aggregate replacement - Saaidin, Syazwi Hakimi (2021)
Natural fine aggregate materials are commonly used in the development and commercial construction in Malaysia yet concrete production increased as linear with the growing Malaysia economy. However, an issue of concrete production was to locate adequate sources of natural fine aggregates. Therefore, this study will promote the utilization of fine recycled concrete aggregate (FRCA) and fine crumb rubber (FCR) as suitable materials to be partial fine aggregates replacement materials in the construction industry. Until today, only a few researchers have done their studies for the effect of the combination of FRCA and FCR as partial fine aggregates replacement materials towards the strength properties of concrete. Therefore, this research is to study the strength properties of concrete containing a combination of FRCA and FCR as partial fine aggregates replacement materials. The design replacement of FRCA which is 0%, 15%, 30%, 45% and 60% and FCR of 0%, 1.5%, 3%, 4.5% and 6% were evaluated. Other than that, the water-cement ratio that was used in this research is 0.5. The test that involved is workability, density, compressive strength, tensile strength, and water absorption tests. In conclusion, the workability and splitting tensile strength of the concrete decreased with the increasing of FRCA and FCR in concrete while the compressive strength was improved. Besides, the percentage of water absorption increased as for FRCA are capable of absorbing water but not for FCR. Based on the result in this study it was found that the optimum percentages of FRCA was at 30% and FCR was at 1.5. Design-Expert software was used for Response Surface Method (RSM) analysis to validate the optimum percentages of FRCA and FCR as partial fine aggregate replacement in concrete. This research can contribute to reduces the amount of waste sent to landfills and incinerators.